Os caminhos da violência letal com motivação LGBTfóbica no Estado do Piauí 2018-2021 - Santos, Carlos Daniel da Silva (2022)
The present work sought to build an analysis framework that explained the contours and paths of lethal violence with LGBTphobic motivation in the State of Piauí, which is called in this research as a crime due to gender prejudice. For this purpose, reports on crimes against the LGBTQIA+ population, produced by newspapers and online news portals, were used, in order to understand how this specific type of violence is structured who are the preferred victims of this criminal type. Only reports of lethal crimes are present in this research, other criminal types were not addressed, given that the objective of the research was to seek to understand the forms and ways in which these crimes with LGBTphobic motivation are configured, their contours, the way in which they reach the victims and who are these victims of LGBTphobic violence in the State of Piauí. Crimes that happened between the years 2018-2021 were analyzed. In the State of Piauí, the process of building the issues of recognition, visibility and guaranteeing the rights of the LGBTQIA+ population is accompanied by a significant increase in violence rates. Therefore, it is necessary to understand the paths and contours of violence motivated by prejudice in crimes committed in the State. In general terms, our reflections were affiliated with the already classic perspectives of studies on power, sexuality and gender, operationalizing the concepts of violence, crime by prejudice and LGBTphobic violence.